Identifikasi Pencemaran Merkuri di Tanah Lokasi Aktivitas dan Pasca Aktivitas Penambangan Emas Tanpa Izin di Desa Roko Kabupaten Halmahera Utara - Margaretha Tabita Tuny; Kurnia Kurnia; Tania Ayu Sudrajat; Kres Mahudin; Melisa Ganna; Defrit Luma (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2023)
Research has been carried out with the title identification of mercury pollution in soil at activity locations and post-unlicensed gold mining (PETI) activities in Roko Village, North Halmahera Regency, with the aim of determining the level of pollution and distribution of mercury at PETI and post-PETI activity locations. Sampling used the proportional sampling method in which 5 soil samples were taken at each location. Soil pH measurements were carried out in situ using a Soil Survey Instrument. To analyze mercury concentration in soil, soil samples were taken, preserved, prepared and tested for mercury concentration using a mercury analyzer. The analysis results show that the pH category at the PETI activity location is in the acid category with a pH range of 4.5-5. Meanwhile, the soil pH at the post-PETI location is in the acid to slightly acid category, namely pH 5-6. The results of the analysis of mercury concentrations in the soil at the PETI location ranged from 3.21 mg/kg - 74.99 mg/kg and post-PETI activity locations ranged from 1.76 mg/kg - 167.1 mg/kg at a radius of 0-50 m and has exceeded the normal criteria for mercury in soil and reached the very critical criteria category.